2016
DOI: 10.1002/star.201500249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic modifications and botanical source on starch–stearic acid complex formation

Abstract: Linear starch forms inclusion complexes with hydrophobic compounds, and the complexation is affected by many factors, such as the degree of polymerization (DP) of linear starch. Enzymatic modification of starch may create more linear starch with favorable DPs that could enhance starch‐inclusion complexation. Starches from different botanical sources, including potato, common corn, and high amylose corn starch (Hylon VII, ∼70% amylose), were modified enzymatically using isoamylase alone or combined with β‐amyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Acetylation did not change the profiles of both starches; the β‐amylase treatment resulted in starch chains of a narrower DP distribution with increased proportions of long DP chains for both acetylation levels of both starches (Figure C and 1D). The molecular size distributions showed that potato amylose appeared at a shorter RT and consequently had a larger molecular size than Hylon VII amylose, agreeing with previous studies . Nevertheless, the proportion of long DP chains was greater in Hylon VII.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Acetylation did not change the profiles of both starches; the β‐amylase treatment resulted in starch chains of a narrower DP distribution with increased proportions of long DP chains for both acetylation levels of both starches (Figure C and 1D). The molecular size distributions showed that potato amylose appeared at a shorter RT and consequently had a larger molecular size than Hylon VII amylose, agreeing with previous studies . Nevertheless, the proportion of long DP chains was greater in Hylon VII.…”
Section: Resultssupporting
confidence: 90%
“…The available studies on the complexation of starch with phenolic compounds have not reported the effect of starch molecular size on the complexation yield . The amylose DP involved in the complexation with fatty acids was suggested to be less than 400 but greater than 20, assuming that starch chains of DP >400 would not form a stable helix, but DP <20 was too short to induce the helical conformation. The present results indicate the importance of both acetylation and DP range on enhancing complexation, and there was a different combination of DS of acetylation and DP of starch chains for the formation of soluble complexes versus insoluble complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Starch DP involved in complexing with fatty acids was suggested to be greater than 20 but less than 400 . Starch chains greater than DP 400 were believed to be too long to form an ordered helical structure, but starch chains less than DP 20 were too short to induce helical structure.…”
Section: Resultsmentioning
confidence: 99%
“…β‐amylase may also be used to reduce the size of amylose chains. Numerous studies have reported that debranching of starch can enhance complex formation (Arijaje & Wang, 2016; Cheng et al., 2015; Hasjim et al., 2010; Reddy et al., 2018; Wang, Hasjim, Wu, Henry, & Gilbert, 2014; Zhang, Huang, Luo, & Fu, 2012). For example, formation of complexes with FAs was significantly improved with starches (high‐amylose MS, potato starch, and MS) that were debranched using pullulanase or isoamylase (Cheng et al., 2015; Hasjim et al., 2010; Reddy et al., 2018; Zhang et al., 2012).…”
Section: Preparation Of Starch–lipid and Starch–lipid–protein Complexesmentioning
confidence: 99%
“…For example, formation of complexes with FAs was significantly improved with starches (high‐amylose MS, potato starch, and MS) that were debranched using pullulanase or isoamylase (Cheng et al., 2015; Hasjim et al., 2010; Reddy et al., 2018; Zhang et al., 2012). An additional β‐amylase treatment of debranched potato and MSs by isoamylase significantly increased complexation between starch and stearic acid (SA) (Arijaje & Wang, 2016). Thus, many studies have shown that there is an optimal linear glucan chain length that facilitates formation of complexes with lipids.…”
Section: Preparation Of Starch–lipid and Starch–lipid–protein Complexesmentioning
confidence: 99%